ANAK SEBAGAI PELAKU TINDAK PIDANA KEKERASAN SEKSUAL BERLANJUT - Nur Alfiyyah Fakhira (2023)
At present, cases of sexual violence continue to show an alarming number. It can even be said that Indonesia has entered a state of emergency for sexual violence. What is more worrying is that sexual violence does not only involve adults but also involves children as perpetrators. In the last three years, the involvement of children as perpetrators of sexual violence has reached more than 200 cases. The purpose of this research is to find out the factors that encourage children to commit crimes of sexual violence and the role of legal handlers in resolving cases of child sexual violence. The method used by the author in this study is a normative-juridical research method. Based on the research conducted, sexual violence committed by children is the result of the implementation of several factors, both in terms of psychological, sociological, and juridical acceptance by children. These factors then instill a negative mindset in the child, encouraging him to act uncontrollably. Then, handlers of children as perpetrators of sexual violence refer to the juvenile justice system, which requires children to be legally responsible for their actions. Furthermore, handling through the coaching process is sought to optimize law enforcement goals. The results of the research also show that there is a need for intensive contributions from the parties to increase awareness and monitor the behavior of children who are at risk of sexual violence.